Caracterização da caatinga e comportamento ingestivo de caprinos - Oliveira, Fábio Luiz de (2018)
The aim of this work was to evaluate the influence of different seasons on the ingestive behavior, on the botanical composition of the diet of goats grazing in the caatinga and on the availability and quality of forage of the caatinga. Four castrated male goats were used, with a mean weight of 30.2 kg and mean age of 20 months. The experiment had a duration of 12 months, comprising two rainy seasons and one dry season, and the treatments consisted of the three seasons (the two rainy seasons were treated separately) with 3 repetitions per season. Each animal was always accompanied by the same observer. The observed behaviors were feeding, idleness, rumination, displacement, social interaction and water intake. Forage collections were performed at 30 points in the area, considering a maximum collection height of 1.5m. All the forage collected and classified in the different strata (herbaceous, woody and litter), after the analysis was performed to know the bromatological composition of these. Non-parametric tests of Kruskal-Wallis (5%) and Nemenyi (5%) were performed in order to identify differences in the occurrence of behaviors between each season of the year. There was no significant difference (P≥0.05) between rumination, displacement and others (sum of social interaction and water intake) in the different seasons. However, a significant difference was observed in the occurrence of feeding and idleness (P = 0.0015 and P = 0.0001, respectively). In the dry season, a higher feeding occurrence and less occurrence of idleness occurred, contrary to what occurred in the rainy season/18 where there was greater occurrence of idleness and less feeding. The woody stratum presented the best bromatological composition, however the stratum was less present, and the herbaceous stratum was more available during the experimental period. The species whose consumption was recorded were: pinhão (jatropha molissima), velande (Croton heliotropiifolius), catingueira (Poincianella pyramidalis), marmeleiro (Croton blanchetianus), pereiro (Aspidosperma pyrifolium), macambira (Bromelia laciniosa), umburana (Commiphora leptophloeos) maniçoba (Manihot glaziovii), besides the herbaceous stratum, litter and cactaceae, the latter consisting of clusters of species of the same habit of growth. Most of the food in the rainy season/17 consisted of the herbaceous stratum (67.47%), in the dry season consisted of litter (56.12%) and in the rainy season/18 consisted of macambira (61.13%). The seasons influenced the pattern of behavior, the choice of food and the availability and quality of forage found in the caatinga.